The influence of short-term quercetin supplementation on peak oxygen uptake during simulated altitude exposure in trained cyclists - Carlstrom, J. A. (International Journal of Exercise Science, 2015)
Endurance performance and peak oxygen uptake (VO2peak) decline as altitude increases. Some data exist suggesting that quercetin supplementation improves aerobic capacity in trained and untrained individuals at sea-level (normobaric normoxic conditions). Few studies have examined the effects of quercetin on endurance performance during simulated altitude exposure (normobaric hypoxic conditions). The purpose of this study was to determine the effects of consuming 1000 mg·day-1 of quercetin for two weeks on cycling VO2peak in healthy trained male cyclists performing under normobaric normoxic and hypoxic conditions (NP and HP, respectively). Fourteen age-matched healthy male subjects were randomized to either a placebo or quercetin group. Baseline and post supplementation VO2peak values were quantified during incremental cycling under normobaric normoxic (FIO2 = 20.9%) and normobaric hypoxic (FIO2 = 13.6 + 0.2%) conditions. Subjects consumed capsules twice daily with either 500 mg quercetin or placebo (Tang) for two weeks and were re-assessed. Test order was randomized and assessments were separated by 48-72 hours. At baseline, there were no significant differences between groups for VO2peak normobaric normoxic trials (NPbaseline Placebo vs. NPbaseline Quercetin = 58.7+8.8 and 61.5+7.9 ml . kg-1 . min-1, respectively, p = 0.541) and normobaric hypoxic trials (HPbaseline Placebo vs. HPbaseline Quercetin = 48.5+8.3 and 50.8+4.8 ml . kg-1 . min-1, respectively, p = 0.534). No significant differences were found after treatment (Placebo: NPbaseline vs. NPpost = 58.7+ 8.8 and 56.7+7.4 ml . kg-1 . min-1, respectively, p = 0.10; HPbaseline vs .HPpost = 48.5+8.3 and 47.1+8.3, respectively, p = 0.50; Quercetin: NPbaseline vs. NPpost = 61.5+7.9 and 62.4+7.3 ml . kg-1 . min-1, respectively, p = 0.558; HPbaseline vs. HPpost = 50.8+4.8 and 51.2+3.8 ml . kg-1 . min-1, respectively, p= 0.656. These data suggest that short-term quercetin supplementation at 1000 mg . day-1 does not affect VO2peak elicited via incremental maximal cycle testing under normobaric normoxic and hypoxic conditions in trained male cyclists. Furthermore, quercetin supplementation did not attenuate the decline in VO2peak that was evident in the normobaric hypoxic condition